2011
DOI: 10.1093/annonc/mdq309
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity, age and overall survival in cetuximab-treated patients with advanced colorectal cancer (ACRC)—results from NCIC CTG CO.17: a phase III trial of cetuximab versus best supportive care

Abstract: Background:The interplay between comorbidity, age and performance status (PS) as predictors of outcome in advanced colorectal cancer (ACRC) is poorly understood. We examined these factors as predictors of treatment toxicity and outcome in cetuximab-treated patients with ACRC.Patients and methods: Comorbidity was independently evaluated using the Charlson Comorbidity Index (CCI), a validated measure of comorbidity based on the presence of medical conditions weighted according to their effect on mortality. CCI s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 43 publications
1
18
0
1
Order By: Relevance
“…The observed safety profile was as expected and the percentage of severe skin reactions, diarrhoea and hypomagnesaemia were similar than those observed with single-agent cetuximab in a non-frail elderly population [11]. Age and comorbidities have previously been analysed in pre-treated patients receiving single-agent anti-EGFR monoclonal antibody [33]. In the trial that compared cetuximab versus best supportive care, comorbidity was independently evaluated using the Charlson Comorbidity Index [33].…”
Section: Discussionmentioning
confidence: 53%
“…The observed safety profile was as expected and the percentage of severe skin reactions, diarrhoea and hypomagnesaemia were similar than those observed with single-agent cetuximab in a non-frail elderly population [11]. Age and comorbidities have previously been analysed in pre-treated patients receiving single-agent anti-EGFR monoclonal antibody [33]. In the trial that compared cetuximab versus best supportive care, comorbidity was independently evaluated using the Charlson Comorbidity Index [33].…”
Section: Discussionmentioning
confidence: 53%
“…As compared with patients in the supportive-care alone group, patients receiving CETUX had a statistically significantly higher incidence of rash of any grade (88.6% vs. 16.1%, p<0.001); infection without neutropenia (12.8% vs. 5.5%, p=0.003); hypomagnesaemia of any grade (5.8% vs. 0%, p<0.001); and infusion reactions of any grade (20.5% vs. 0%, p<0.001) [14]. In a separate analysis of the same phase III trial the impact of co-morbidity, age and performance status on the efficacy and toxicity in CETUX treated patients was examined [15]. Age was not significantly associated with OS either in a uni-or multivariate analysis.…”
Section: Cetuximabmentioning
confidence: 99%
“…It is very common, with up to 88% of patients experiencing a rash, but with most events being grade 1 and 2 [20]. Severe infusion reactions may occur in 1.4% to 4.5% [13,15,21], but it seems that they can be reduced by giving premedication with antihistamines and corticosteroids [22]. Hypomagnesaemia is a common side effect of CETUX that may occur in half of the patients receiving the treatment, with grade 3 and 4 events in as many as 25% of patients [23,24].…”
Section: Cetuximabmentioning
confidence: 99%
“…Moreover, when combination chemotherapy is initiated in elderly patients, its efficacy is comparable to that in younger patients, as noted by similar response rates and pfs with folfiri use in patients more than 70 years of age compared with those 70 years of age and younger 46 . In fact, studies investigating the effects of age and comorbidity on survival have identified a significant correlation of comorbidity score with survival and a correlation of age with comorbidity burden, but no effect of increasing age on survival 47 . A retrospective study by Aparicio and colleagues 48 in patients 75 years of age and older (n = 110) showed, as other independent risk factors for poor survival, the presence of metastasis (hazard ratio: 3.9; 95% ci: p = 0.005) and cci score greater than 3 (hazard ratio: 28.9; 95% ci: 2.5 to 335.6; p = 0.001).…”
Section: Discussionmentioning
confidence: 99%